A COMPARISON BETWEEN INTRA-ARTICULAR 0.2% ROPIVACAINE AND 0.25% BUPIVACAINE FOR POST-OPERATIVE ANALGESIA FOLLOWING DAY-CARE ARTHROSCOPIC KNEE SURGERIES - P H, Sai Kaushik; Kamath, Shaila S; Kaminuath, Surendra U (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objective is to compare the effectiveness of intra-articular injection of ropivacaine and bupivacaine in providing pain relief after arthroscopic knee surgery. Methods: A total of 60 patients of both genders aged 20â€“60 years, the American Society of Anesthesiologists physical Status I and II, undergoing day-care arthroscopic knee surgery under spinal anesthesia, were assigned into two groups randomly. Group 1 received 10 ml of 0.2% ropivacaine, while Group 2 received 10 ml of 0.25% bupivacaine intra-articularly at the end of the procedure. Pain was assessed for 24 h postoperatively using visual analog scale (VAS) and diclofenac sodium given as rescue analgesia when VAS >3. Time of first analgesic request and total rescue analgesic were noted and compared. Statistical analysis used: Students unpaired t-test and Chi-square test and Mannâ€“Whitney test Zâ€ value wherever appropriate. A p<0.05 was considered statistically significant. Results: Based on comparable demographic profiles, time for the requirement of first post-operative rescue analgesia (262.43Â±57.13 vs. 256.30Â±44.4) min and total mean rescue analgesic requirement was 152.50Â±57.367 vs. 142.50Â±41.07 mg in Groups 1 and 2, respectively. Group 1 showed slightly prolonged duration of analgesia, but total analgesic requirement was more than Group 2. However, comparing the duration of analgesia and total analgesic requirement showed no statistically significant difference between the groups (p>0.05). Conclusion: Both ropivacaine and bupivacaine injected intra-articularly have similar efficacy statistically in relieving post-operative pain in day-care arthroscopic knee surgery.